Epigenetics - Gottschling, Daniel E.; Felsenfeld, Gary; Jenuwein, Thomas; Allis, C. David; Allis, C. David; Jenuwein, Thomas; Reinberg, Danny; Reinberg, Danny; Caparros, Marie-Laure (Cold Spring Harbor Laboratory Press, 2007)
The regulation of gene expression in many biological processes involves epigenetic mechanisms. In this new volume, experts in the field discuss epigenetic effects from many perspectives. This book is a major resource for those working in the field or in advanced courses. Epigenetics : from phenomenon to field p. 1 A brief history of epigenetics p. 15 Overview and concepts p. 23 Epigenetics in Saccharomyces cerevisiae p. 63 Position-effect variegation, heterochromatin formation, and gene silencing in Drosophila p. 81 Fungal models for epigenetic research : Schizosaccharomyces pombe and Neurospora crassa p. 101 Epigenetics of ciliates p. 127 RNAi and heterochromatin assembly p. 151 Epigenetic regulation in plants p. 167 Chromatin modifications and their mechanism of action p. 191 Transcriptional silencing by polycomb group proteins p. 211 Transcriptional regulation by trithorax group proteins p. 231 Histone variants and epigenetics p. 249 Epigenetic regulation of chromosome inheritance p. 265 Epigenetic regulation of the X chromosomes in C. elegans p. 291 Dosage compensation in Drosophila p. 307 Dosage compensation in mammals p. 321 DNA methylation in mammals p. 341 Genomic imprinting in mammals p. 357 Germ line and pluripotent stem cells p. 377 Epigenetic control of lymphopoiesis p. 397 Nuclear transplantation and the reprogramming of the genome p. 415 Epigenetics and human disease p. 435 Epigenetic determinants of cancer p. 457 WWW Resources p. 477 Histone modifications and references p. 479